Field evaluation of Trichoderma and fungicides for the management of castor Fusarium wilt disease: Field evaluation of Trichoderma and fungicides for the management of castor Fusarium wilt disease - M DEIVAMAN; S R VENKATACHALAM; P ARUTCHENTHIL; P KATHIRVELAN; M SENTHILKUMAR; B GEETHA (Journal of Oilseeds Research, 2020)
Field efficacy of Trichoderma and fungicides was tested for castor Fusarium wilt management. Among the seventreatments, seed treatment with carboxin 37.5% + Thiram 37.5% @ 3g/kg was found superior. Also the combined seed and soil application of T. harzianum, Th4d 1.5% WP was best among Trichoderma applications.